The Influence of Implementing An Integrated Education System and Diniyah Teacher Motivation On The Quality Of Education In State Private High Schools In Aceh Besar - Zulaikhaa Zulaikhaa; Lili Kasmini; Mulia Putra (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to analyze the influence of the implementation of an integrated education system and the motivation of diniyah teachers on the quality of education in state junior high schools in Aceh Besar. The research approach that will be used is a quantitative approach. This research uses a type of causal association approach, namely causality (cause-effect). Based on the results of the research that has been carried out, it can be concluded that the integrated school education system has a positive and significant influence on the quality of Aceh Besar State Junior High School education. The large percentage of the second contribution can influence teacher performance by 12.3%. The T test calculation shows that Fcount is 4.401 which is greater than Ftable which is 3.150 (Fcount> Ftable) which means the multiple regression value is significant. Thus, the integrated education system and the motivation of the diniyah teachers simultaneously influence the quality of education at the Aceh Besar State Junior High School.